2008
DOI: 10.1088/0957-0233/19/5/055702
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal guided waves for monitoring corrosion in reinforced mortar

Abstract: Guided longitudinal modes in both low (<200 kHz) and high (2–8 MHz) frequency ranges were invoked to monitor damage in reinforced mortar specimens undergoing accelerated uniform corrosion. The fundamental longitudinal mode, i.e. L(0, 1), and the L(0, 9) mode were invoked for low- and high-frequency testing, respectively. Because of the significant amount of axial displacement at the steel/mortar interface, the L(0, 1) mode was so appreciably attenuated for the particular specimen size used that it is was not d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 21 publications
0
34
0
Order By: Relevance
“…Na et al [8,14,15] utilized the guided waves for the inspection of steel-concrete interfaces and glass fiber polymer-concrete interfaces. Ervin et al [16,17] used both low (<200 kHz) and high (2)(3)(4)(5)(6)(7)(8)(9) guided longitudinal modes to ultrasonically monitor the accelerated corrosion experiments. It was found that some modes were sensitive to the combined effect of bond deterioration and mortar stiffness reduction while some other modes related well to change in crosssectional area.…”
Section: Introductionmentioning
confidence: 99%
“…Na et al [8,14,15] utilized the guided waves for the inspection of steel-concrete interfaces and glass fiber polymer-concrete interfaces. Ervin et al [16,17] used both low (<200 kHz) and high (2)(3)(4)(5)(6)(7)(8)(9) guided longitudinal modes to ultrasonically monitor the accelerated corrosion experiments. It was found that some modes were sensitive to the combined effect of bond deterioration and mortar stiffness reduction while some other modes related well to change in crosssectional area.…”
Section: Introductionmentioning
confidence: 99%
“…The leakage depends on the relative elastic and damping properties of the surrounding concrete layer [41]. Thus, the steel-concrete interface can be characterized by ultrasonic investigations [41][42][43][44][45][46]. As concrete sets and hardens, the bond between the reinforcing bar and the surrounding concrete improves.…”
Section: Guided Waves In Reinforcing Bars In Concretementioning
confidence: 99%
“…Thus, simulation of corrosion of rebars has been attempted by researchers. It has been simulated in various ways such as by introducing delamination between steel and concrete by using Poly-Vinyl Chloride (PVC) sleeves or by wrapping a soft tape on the bars [43,44]. Debonding impedes the leakage of waves into the surrounding concrete and causes increase in the signal strength at the receiving end.…”
Section: Corrosion In Rc Structures and Monitoring By Guided Wavesmentioning
confidence: 99%
“…It indicates increasing corrosion by loss of bond between steel and concrete. Both low and high frequency guided wave modes to monitor corrosion damage in reinforced mortar specimens have been attempted [44,45]. Corrosion has been simulated by artificially incorporating debonds and notches and has been compared with actually corroded specimens successfully [32].…”
Section: Corrosion In Rc Structures and Monitoring By Guided Wavesmentioning
confidence: 99%